2018
DOI: 10.4028/www.scientific.net/ssp.284.936
|View full text |Cite
|
Sign up to set email alerts
|

Creep and Long-Time Strength of Compression Elements from Foam Concrete

Abstract: In this article discusses the mechanical properties of foam concrete, which submitted based on the experimental data of long force resistance and deformation of compression elements from foam concrete. Also submitted criterion range of strength and deformation characteristics of foam concrete different structural modification with taking into account the permanently acting load, which necessary for calculation and design structures of buildings. In article such characteristics of foam concrete as durability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
0
0
1
Order By: Relevance
“…When analyzing experimental creep specific strain curves at different relative stress levels, it was found that up to relative stress levels of 0,60 and 0,45 Rbm, respectively for fine-grained and micrograined foam concrete, creep deformations develop linearly [16,17]. At higher stresses, the dependence of creep deformations of foam concrete on compression stresses is non-linear.…”
Section: Results Of Experimental and Theoretical Studiesmentioning
confidence: 99%
“…When analyzing experimental creep specific strain curves at different relative stress levels, it was found that up to relative stress levels of 0,60 and 0,45 Rbm, respectively for fine-grained and micrograined foam concrete, creep deformations develop linearly [16,17]. At higher stresses, the dependence of creep deformations of foam concrete on compression stresses is non-linear.…”
Section: Results Of Experimental and Theoretical Studiesmentioning
confidence: 99%
“…Deformations of creep of foam concrete depend on age by the time of loadcase, decreasing at increase in the last. It is established that the theory of elastic and creeping body fairly describes processes of creep and after-effect of foam concrete [14]. Analytical processing of results of experimental data will be coordinated with the models of the theory of elastic and creeping body offered by S.V.…”
Section: Results Of Experimental and Theoretical Studiesmentioning
confidence: 99%
“…Studying of deformations of creep was carried out with the broad range of voltage levels of compression that gave the chance to reveal full picture of deformation of foam concrete. The testing procedure of compressed elements is lit in works [13][14]. The technique of testing of beams for bend the loading enclosed in 1/3 flights from support with the scheme of installation of devices and sticking-up of tensoresistors for measurement of deformations, is given in work [15].…”
Section: Methodical Provisions Of Experimental Studiesmentioning
confidence: 99%
“…Сегодня разделение несущих и теплоизолирующих функций строительных материалов в конструкциях зданий является основой концепции теплоэффективного здания и повышения уровня его тепловой защиты [1][2][3][4][5]. Принимая это во внимание, в последнее время значительно возросла роль ячеистых газо-и пенобетонов, которые находят все более широкое и комплексное применение, не только как теплоизоляционный, но и как эффективный конструкционный материал для несущих конструкций зданий [6][7][8][9][10][11][12][13][14].…”
Section: вводная частьunclassified